Analysis of Critical Thinking Skills of Grade IX Students in Opportunity Material Reviewed from Self-Regulated Learning - Findi Auliya Fatikhah; Fitriyani; Gunawan; Ahmad; Kusno (Universitas Teknokrat Indonesia, 2025)
Critical thinking skills are very important and closely related to how students manage their learning process independently. The purpose of this study is to analyze the ability to think critically on opportunity materials reviewed from self-regulated learning in junior high school students in grade IX. The method used is qualitative with a descriptive approach. The research was carried out at Putra Harapan Boarding School Purwokerto with the research subject grade IX students. The research instruments used were in the form of essay questions designed based on indicators of critical thinking ability and self-regulated learning (SRL) questionnaires. Based on the students, they are grouped into high, medium, and low categories. Respondents were taken one student from each category by purposive sampling. Data analysis includes reduction, data presentation, and Conclusions. The results of the study were that students in the high SRL category met the achievement of correct and complete critical thinking skills. Students in the SRL category are meeting the critical thinking indicators appropriately but need to emphasize the aspect of argument analysis. In contrast, low SRL students cannot achieve complete critical thinking skills.